COREELATION BETWEEN LEADERSHIP STYLE AND EMPLOYEE PERFORMANCE IN THE MANAGEMENT DEPARTMENT OF RSNU TUBAN BASED ON PATH GOAL THEORY - Surotul Ilmiah; Sugiyono (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Leadership is a universal phenomenon in collective life, playing a central role in organizational and group dynamics. To achieve common goals, individuals within an organization need to foster unity by following the guidance of their leader. Leadership style is the way a leader performs their role in directing subordinates. This study aims to analyze the relationship between leadership style and employee performance in the management department of RSNU Tuban. A quantitative, analytical, correlational method was employed through an observational approach with a cross-sectional time frame. The study population comprised 130 employees, with a sample of 97 respondents selected through simple random sampling. The independent variable was leadership style, while the dependent variable was employee performance in the management department of RSNU Tuban. Data analysis used the Spearman test. The data collection results indicate a significant relationship between leadership style and employee performance, as evidenced by an Asymp Sig (2-sided) value of 0.000. A lower p-value signifies a higher level of significance in the study. This means the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. The findings underscore a significant relationship between leadership style and employee performance in the management department of RSNU Tuban.